“Elaboración de una bebida a partir de lactosuero y pulpa de arazá (Eugenia Stipitata) con edulcorantes naturales” - Quintana Carua, Evelyn Estefania (2023)
This research project was carried out in order to make a drink from whey and arazá pulp with the addition of natural sweeteners (panela, honey and brown sugar), applying a Completely Random Block Design (DBCA). under a factorial arrangement A*B (3*3) where two factors are presented, factor A based on the whey and arazá pulp ratio at three levels and factor B based on the types of natural sweeteners. Once the treatments were carried out at different concentrations and with the corresponding repetitions, the physical-chemical parameters such as pH, soluble solids and titratable acidity were measured for each of the formulations, taking the measurements for 7 days after processing. Using the statistical tool InfoStat, the data obtained was analyzed and once the results of the statistical analysis were interpreted, the best formulation t5 (a2b2) that corresponds to the relationship (50% whey, 50% arazá pulp + honey) was determined. The sensory analysis was carried out on 10 untrained judges with agro industrial knowledge, a descriptive method was applied and with values from 1 to 5 according to a hedonic scale, attributes of flavor, color, smell, appearance and acceptability in the drink were evaluated, determining that the best formulation corresponds to treatment t5 (a2b2). In the best treatment, physicochemical parameters were obtained with a pH of 3,6, soluble solids of 11.91 °Brix and titratable acidity of (0,07 %); a nutritional analysis with values of protein 0,79 %, fat 0,83 %, crude fiber 0,00 %, total sugars 11,28 %, carbohydrates 13,87 %, ash 0,42 %, potassium 104,74 (mg /100g), sodium 27,88 (mg/100g), calories 66,11 (kcal/100g), cholesterol 2,7 (mg/100g), vitamin A 754,87 (IU/mg), vitamin B1 0,05 (mg/100g), vitamin C 1,63 (mg/100g) and a microbiological analysis with count of total Coliforms in (<10 UFC/ml), Total Mesophilic Aerobes. Compared with the Ecuadorian Technical Standard (NTE INEN 2304, 2017) for soft drinks or non-carbonated drinks, (NTE INEN 2564, 2011) for dairy drinks and (NTE INEN 2609, 2012) for whey drinks, these parameters comply with the specifications and requirements established by each revised standard, therefore, a drink with optimal conditions for consumption and with a significant nutritional level is obtained. The retail price of the 500 ml drink is $1,85 cents. Being a price that is acceptable to the consumer.